Imaging nuclear motion during the photofragmentation of halomethane molecules triggered by ultraviolet light - Ziaee, Farzaneh (Kansas State University, 2022)
Understanding the photoexcitation of molecules and visualizing the ensuing dynamics on their natural time scale is essential for our ability to describe and exploit many fundamental processes in different areas of science and technology. Prominent examples of such processes include, among many others, the adverse impacts of different classes of molecules on the ozone layer in atmospheric chemistry, light conversion into electricity through photovoltaics, photocatalysis, and some essential biological processes like vision and photosynthesis. Studies of molecular dynamics triggered by photon-molecule interaction underpin our understanding of many of these phenomena by adding the intermediate state to the “before-and-after” view of such photochemical or photobiological reactions. While identifying the initial molecular structure at equilibrium and determining the final products are crucial steps for the reaction characterization, understanding the dynamics connecting these initial and final states is essential for comprehending how the reaction really happens and potentially controlling its outcome. In other words, besides the “static” view of photo-induced reactions, identifying all intermediate states involved and mapping their spatio-temporal evolution are of great interest and importance. Since photoexcitation often induces coupled electron and nuclear motion on Angström spatial and femtosecond time scales, resolving such dynamics in space and time represents a significant scientific and technological challenge. Experimental tools to address this challenge have recently become available with the development of femtosecond lasers and imaging techniques capable of visualizing the evolving molecular structure. The present thesis aims to investigate the photodissociation dynamics of halomethane molecules triggered by ultraviolet (UV) light using coincidence ion momentum imaging as a primary structural characterization tool. Halomethanes are often considered as prototypical systems for molecular photodissociation in the UV domain. Due to the complicated excited-state structure driving the photochemistry of these molecules, they exhibit rich dynamics while being small enough to still allow for a detailed theoretical treatment. The primary goal of this work is to disentangle the photo-induced reaction channels, including direct and indirect dissociation pathways, and to visualize the motion of the individual molecular fragments in each of these channels. The photofragmentation reactions considered here include two- and three-body dissociation, transient isomerization and molecular halogen formation. The experiments are carried out at two different excitation wavelengths, 263 nm and 198 nm, which enables varying the dominant reaction pathways. To carry out these measurements, the 3rd and 4th harmonics of a 790 nm Ti: Sa femtosecond laser are used to initiate the dynamics of interest, which are then probed by multiple ionization and Coulomb explosion induced by an intense 790 nm pulse arriving after a variable time delay. The ions created in such pump-probe experiments are detected employing COLd Target Recoil Ion Momentum Spectroscopy (COLTRIMS). To facilitate interpreting the experimental results, they are compared to an extensive set of Coulomb explosion simulations. More specifically, this thesis describes three major studies. The first one is a set of time-resolved measurements on iodomethane (CH₃I) photodissociation in the A-band, one of the best-studied reactions in ultrafast photochemistry. Here, the focus is on a detailed characterization of direct dissociation dynamics by Coulomb explosion imaging (CEI) and disentangling the competing reaction pathways involving single- and multi-photon excitations. The coincident measurement mode and an improved time resolution of 40-45 fs allowed us to observe a new feature in the two-body CEI pattern of this well-studied reaction, which was predicted theoretically but not yet observed experimentally, and to identify signatures of two- and three-photon processes populating Rydberg and ionic states. The second part of this work focuses on time-resolved studies of bromoiodomethane (CH₂BrI) and chloroiodomethane (CH₂ICl) photofragmentation in the A-band at 263 nm and, in particular, on imaging the co-fragment rotation. Here, the main objectives are to evaluate the effects of halogen-atom substitution on molecular dynamics and map the time evolution of individual photodissociation pathways. For these molecules, photoabsorption in the A-band predominantly breaks the C-I bond, with weaker but non-negligible contribution from the C-Br (or C-Cl) bond cleavage. Coincident two-body CEI analysis is used to map both of these channels, as well as a minor contribution from molecular halogen (IBr or ICl) formation. Three-body CEI patterns offer a deeper insight into the dynamics of these reactions and, in addition, reveal clear signatures of the three-body dissociation, which – at this wavelength – is most likely driven by the two-photon absorption. The three-body analysis also suggests that some fragmentation pathways pass through a transient linearized configuration, which is reached within ~100 fs from the initial photoabsorption and decays on a comparably fast time scale. One of the interesting aspects of dihalomethanes photodissociation in the A-band is that, unlike CH₃I, where the excess energy is primarily channeled into translational motion, a significant portion of the available energy is partitioned into rotational excitation. Carbon-halogen bond cleavage results in the rotation of the molecular co-fragment, which can be unambiguously traced in the coincident three-body CEI maps for the corresponding dissociation channel. In this work, such rotational motion is directly imaged for the dissociation of either halogen atom, resulting in a “molecular movie” of the dissociating and rotating molecule. The third group of experiments described in this thesis includes time-resolved studies of bromoiodomethane and diiodomethane (CH₂I₂) photofragmentation in the B-band at 198 nm. In this part, the main goal is to trace the wavelength dependence of the photochemical reaction pathways. For CH₂BrI, we observe a reversal of the branching ratio of C-I and C-Br bond cleavage compared to the 263 nm data, in agreement with earlier spectroscopic and theoretical studies. However, at 198 nm, three-body dissociation and molecular halogen formation become dominant photofragmentation channels for both molecules. Finally, the CH₃I photodissociation is also studied in the B-band at 198 nm, where the excitation of the lowest-lying Rydberg states is expected to trigger pre-dissociation dynamics. Although no in-depth data analysis and modeling for this reaction have been carried out, the two-body CEI results clearly demonstrate the pre-dissociation nature of CH₃I fragmentation at this wavelength, reflected in a broad, diffuse dissociation band, which is very different from distinct dissociation features observed for direct dissociation processes. Moreover, the data exhibit a pronounced oscillatory structure with a periodicity of 130-140 fs, which is visible only within the pre-dissociation lifetime of the excited state (~1.5 ps). While the exact origin of this structure remains unclear and will be a subject of further analysis and theoretical work, it most likely reflects the bound-state vibrational motion, which lasts until it pre-dissociates. The work presented in this thesis represents a significant step towards a better understanding of the UV-driven photochemistry of halomethanes and contains several examples of direct visualization of the atomic motion during these photochemical reactions. Our experimental approach enabled us to identify and disentangle different dissociation pathways and track their time evolution. The experimental methodology described here can be directly applied to investigate the light-driven nuclear motion in other molecular systems with different light sources.
Keywords: Molecular dynamics; Photodissociation; Coincident ion momentum imaging; Ultraviolet photoexcitation dynamics; Coulomb explosion imaging; Halomethanes